Mechanical and tactile incompatibilities cause reproductive isolation between two young damselfly species. (1st October 2017) - Barnard, Alexandra A.; Fincke, Ola M.; McPeek, Mark A.; Masly, John P.
Abstract: External male reproductive structures have received considerable attention as a cause of reproductive isolation (RI), because the morphology of these structures often evolves rapidly between populations. This rapid evolution presents the potential for mechanical incompatibilities with heterospecific female structures during mating and could thus prevent interbreeding between nascent species. Although such mechanical incompatibilities have received little empirical support as a common cause of RI, the potential for mismatch of reproductive structures to cause RI due to incompatible species‐specific tactile cues has not been tested. We tested the importance of mechanical and tactile incompatibilities in RI between Enallagma anna and E. carunculatum, two damselfly species that diverged within the past ∼250, 000 years and currently hybridize in a sympatric region. We quantified 19 prezygotic and postzygotic RI barriers using both naturally occurring and laboratory‐reared damselflies. We found incomplete mechanical isolation between the two pure species and between hybrid males and pure species females. Interestingly, in mating pairs for which mechanical isolation was incomplete, females showed greater resistance and refusal to mate with hybrid or heterospecific males compared to conspecific males. This observation suggests that tactile incompatibilities involving male reproductive structures can influence female mating decisions and form a strong barrier to gene flow in early stages of speciation.